Variation in the involvement of hippocampal pyramidal cell subtypes in spatial learning tasks - Sharkov, Nadja; Sackmann, Tina; Stevens, Nikolas; Kupke, Janina; Draguhn, Andreas; Oliveira, Ana; Both, Martin (eNeuro, 2025)
Hippocampal pyramidal cells are involved in spatial coding and memory formation. Recent evidence shows that they can be classified according to the origin of their axon, either emerging from the soma (non-AcD for “nonaxon-carrying dendrite”) or from a proximal basal dendrite (AcD). We have shown that AcD neurons account for ∼50% of CA1 pyramidal neurons and that they integrate excitatory inputs differently. They are less susceptible to perisomatic inhibition and more strongly recruited during memory-related network oscillations with strong inhibitory activity. Here, we tested whether AcD and non-AcD neurons are differentially engaged during distinct stages of spatial learning. We trained mice of either sex on a spatial memory task (m-maze) and quantified c-Fos expression in CA1 pyramidal neurons at different training stages. AcD and non-AcD cells were distinguished by staining the axon initial segment. Across learning stages, dorsal and medioventral hippocampus showed distinct activation patterns. In dorsal CA1, c-Fos expression shifted from a predominant presence in non-AcD cells at early stages to the increased presence in AcD cells at later stages. In medioventral CA1, AcD neurons showed a transient c-Fos expression peak at intermediate stages of the training, accompanied by a progressive reduction of the percentage of AcD cells over time. This reduction was not observable in the dorsal hippocampus. This suggests region- and cell type-dependent recruitment patterns of CA1 pyramidal cells during learning and indicates that the site of axon origin may undergo structural plasticity. In addition, the findings support functional and structural differentiation along the dorsoventral axis of CA1.
Online veröffentlicht: 22. Oktober 2025
Gesehen am 27.01.2026